Non-motherhood in Chiapas. Indigenous women who are not mothers - Linares Bravo, Bárbara Carolina (2025)
Introduction: In Chiapas, one of the states in Mexico with the highest proportion of indigenous population, non-motherhood has historically been more frequent among indigenous women, but its exercise has not been sufficiently documented. Methodology: Based on the descriptive analysis of Census information, the socioeconomic and health conditions in which indigenous non-motherhood is carried out in Chiapas are explored. As well as the particularities that it could have with respect to non-motherhood exercised by non-indigenous women. Indigenous people of the entity and the country. Results: Indigenous non-motherhood in Chiapas was presented as a growing trend whose proportions exceeded state and national values in the four decades analyzed, finding singleness as a relevant element that is not explained by migratory factors or any population imbalance. It is practiced under adverse socioeconomic conditions. It is also observed when women have a disability. Conclusions: The coexistence of different forms and conditions of non-motherhood is observed: 1) with high education and economic activity, practiced out basically by non-indigenous women; 2) without schooling and without economic activity, more common among indigenous women, occurring in a higher proportion in Chiapas; and 3) without schooling and with economic activity, with relevant proportions among indigenous women, mainly from Chiapas. The relationship between the absence of children and disabilities shows an important aspect of exclusion among childless women that needs to be observed in greater detail in studies on non-motherhood in Mexico.